MicroRNA-129-5p Regulates Glycolysis and Cell Proliferation by Targeting the Glucose Transporter SLC2A3 in Gastric Cancer Cells - Chen, Di; Wang, Hui; Chen, Jie; Li, Zhe; Li, Shengli; Hu, Zhixiang; Huang, Shenglin; Zhao, Yingjun; He, Xianghuo (Frontiers in Pharmacology, 2018)
Tumour cells increase their glucose consumption through aerobic glycolysis to manufacture the necessary biomass required for proliferation, commonly known as the Warburg effect. Accumulating evidences suggest that microRNAs (miRNAs) interact with their target genes and contribute to metabolic reprogramming in cancer cells. By integrating high-throughput screening data and the existing miRNA expression datasets, we explored the roles of candidate glycometabolism-regulating miRNAs in gastric cancer (GC). Subsequent investigation of the characterized miRNAs indicated that miR-129-5p inhibits glucose metabolism in GC cells. miRNA-129-5p directly targets the 3′-UTR of SLC2A3, thereby suppressing glucose consumption, lactate production, cellular ATP levels and glucose uptake of GC cells. In addition, the PI3K-Akt and MAPK signalling pathways are involved in the effects of the miR-129-5p/SLC2A3 axis, regulating GC glucose metabolism and growth. These results reveal a novel role of the miR-129-5p/SLC2A3 axis in reprogramming the glycometabolism process in GC cells and indicate a potential therapeutic target for the treatment of this disease.